PWE-076 What is the meaning of low lysosomal acid lipase (lal) levels in the hepatology and metabolic clinic?. (17th June 2017) - Pericleous, M; Kelly, C; Wang, T; Livingstone, C; Ala, A
Abstract : Introduction: LAL deficiency (LALd) is a rare autosomal recessive condition of deficiency or underexpression of the enzyme LAL which leads to the excessive accumulation of cholesteryl esters and triglycerides in various organs especially the liver. Patients often present with hepatosplenomegaly, deranged liver function tests (LFTs), hyperlipidaemia, gastrointestinal symptoms, and hepatic failure. LALd is often misdiagnosed as non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), cryptogenic cirrhosis or type IIa or b hyperlipoproteinaemia. Aim: To develop a model for LALd testing in the hepatology and metabolic clinics using dried blood spotting (DBS). Method: We carried out a systematic literature review and worked closely with paediatricians, hepatologists, metabolic consultants and endocrinologists to develop a screening algorithm for LALd. With the support of industry partners, we obtained DBS test kits and started testing suitable patients. The DBS tests were sent for processing to an external laboratory in Glasgow. Results: To date we have tested 122 adult patients (M:F 2.4:1). The mean LAL levels were 0.56 nmol/punch/hour (range 0.08–1.26 nmol/punch/hour) (Figure 1). We identified 27 (22.5%) patients with LAL levels below the reference range (0.37–2.30 nmol/punch/hr). Almost half of these patients were eventually diagnosed with NAFLD/NASH (48.15%) (Figure 2). The control enzyme, beta galactosidase, was used on two occasions to test sample quality and one sample was regarded as of poor quality. Conclusion: The genotype to phenotype presentation has not been clearly elucidated for LALd. More than 40 mutations have been identified each leading to variable enzymatic expression. Traditionally, if the LAL levels are less than 0.15, control enzymes are used to test sample quality. In good quality samples, levels of <0.03 are considered diagnostic. Yet, there is no consensus on interpreting levels between 0.03–0.37. These could be carriers or LALd or patients with mutations allowing expression of adequate levels of LAL. The significance of this observation merits further investigation especially in associating LAL levels with full mutation analysis. Furthermore, the large proportion of low levels of LAL in NASH/NALD patients may suggest an alternative mechanism of fat accumulation in hepatocytes through impaired degradation of cholesteryl esters and triglycerides. Disclosure of Interest: None Declared